2017
DOI: 10.1590/1981-863720170001000053304
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem level of Brazilian teenagers victims of bullying and its relation with the need of orthodontic treatment

Abstract: Objective Results A total of 815 adolescents participated in the study. There was a statistically significant association between self-esteem and the variables: sex (p <.0001), willingness to straighten teeth to improve appearance (p = 0.0006), bullying victim (p <.0001), frequency of bullying = 0.0111) and consequences of bullying (p <.0001). A significant risk factor for non-white adolescents' very negative self-esteem (OR = 1.914) was present together with bullying victims who had had negative consequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 22 publications
2
11
0
7
Order By: Relevance
“…Students who reported negative consequences of episodes of bullying were three times more likely to have a bad OHRQoL. Only one study in Jordan 20 and another one in the United Kingdom 24 showed this negative impact of bullying on the OHRQoL. In the first study, the authors found this association in 11- and 12-year-old students who self-reported episodes of bullying motivated by dentofacial characteristics; however, no oral examination for the presence of malocclusion was performed 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who reported negative consequences of episodes of bullying were three times more likely to have a bad OHRQoL. Only one study in Jordan 20 and another one in the United Kingdom 24 showed this negative impact of bullying on the OHRQoL. In the first study, the authors found this association in 11- and 12-year-old students who self-reported episodes of bullying motivated by dentofacial characteristics; however, no oral examination for the presence of malocclusion was performed 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Assessments of OHRQoL are important for subjective evaluations of the population, 4 as these assessments involve a multidimensional perception of the individual, and the findings of these assessments should be taken into consideration because concerns such as dental aesthetics and psychological well-being are often presented as reasons for seeking orthodontic treatment during childhood and adolescence. 20 …”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al autoconcepto intelectual, es posible que esta dimensión no se vincule estrechamente con las habilidades sociales ya que está más orientado al plano cognitivo e intelectual. 314 Tacca, Se ha encontrado que la relación entre habilidades sociales y autoestima es positiva y mediana, esto coincidiría con Harris y Orth (2019), Ayvar (2017), Gatto et al (2017), Orgilés et al (2017), Thompson et al (2016), Bi et al (2015) y Tajfel (1981). Además, los resultados reflejan que el autoconcepto y la autoestima se relacionan también en forma positiva pero grande, concordando con las propuestas de Massenzana (2017) y Tajfel (1981).…”
Section: Rise -International Journal Of Sociology Of Education 9(3) 311unclassified
“…Según Massenzana (2017), la autoestima es una valoración que realiza el sujeto en base a las autopercepciones que tiene sobre si y, estas últimas, se originan gracias a las experiencias vividas (familiares, sociales, físicas, etc.). Para Gatto et al (2017), la autoestima cumple un rol critico en las relaciones sociales del adolescente. De lo anterior, es posible colegir que la 298 Tacca, autopercepción que construye el individuo está condicionada por el grupo social al cual pertenece; así mismo, el significado emocional y valoración que le atribuye a esas características dependerá del sentido de pertenecía del individuo hacia su grupo social (Tajfel, 1981).…”
unclassified
“…Esta situação ocorre muitas vezes, devido ao comprometimento estético da face, marcado pelo overjet acentuado, em decorrência da projeção maxilar e/ou retrognatismo mandibular, bem como pelas suas interações com as inclinações dentárias e estruturas de tecido mole. Em razão disto, esta tipologia facial acaba gerando perda da autoestima, prejuízo no desempenho escolar, insegurança, bullying, depressão e reclusão comprometendo sua qualidade de vida [6][7][8][9] .…”
Section: Introductionunclassified